Analysis of Service Quality Level of Financing in Bank BTN Syariah Using the Fuzzy SERVQUAL Method (Case Study: Financing Unit of Bank BTN Syariah Balikpapan Branch) - Pambudi, Rifky; Safar Tosungku, La Ode Ahmad; Amelia Pawitra, Theresia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Bank Tabungan Negara (BTN) Balikpapan is a financial institution that collects funds from the public and channels them in the form of credit. The objective of this research is to measure the service quality at Bank BTN Syariah Balikpapan using the SERVQUAL, conduct an analysis using the Fuzzy method to obtain single values that represent each attribute of perceptions and expectations, and formulate improvement proposals to enhance the quality of financing services. The highest gap was found in attribute Q1 "Adequate equipment and technology" with a Gap value of 20.66 (137.38%), while the lowest gap in service quality was found in attribute Q21 "Employees who provide personal attention to customers" with a gap value of -48.51 (38.60%). This indicates that attribute Q21 is an important aspect that needs improvement due to the negative gap between customer expectations and perceptions. Furthermore, the overall measurement of service quality in the financing unit yielded an average gap value of -0.77 (Good Enough). Based on the fuzzy Servqual method, several attributes with the lowest negative gaps in the service quality of Bank BTN Syariah were identified. Proposed improvements include conducting Experiential Training to enhance personal relationship approach with customers, adding training with banking knowledge content to improve the financing process, and providing additional rewards to employees who achieve the desired improvements in service.